Natura urbana : ecological constellations in urban space. - Gandy, Matthew (The MIT Press, 2024)
In Natura Urbana, Matthew Gandy explores the articulation of alternative, and in some cases, counterhegemonic sources of knowledge about urban nature produced by artists, writers, scientists, and other primarily curiosity-driven encounters, including voices seldom heard in environmental discourse.